PENGARUH KONSERVATISME AKUNTANSI, INTENSITAS PERSEDIAAN, INTENSITAS MODAL, DAN INTENSITAS ASET TETAP TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN JAKARTA ISLAMIC INDEX (JII) 70 YANG TERDAFTAR DI BURSA EFEK INDONESIA PADA TAHUN 2021-2023 - Firmansyah, Dino; Afrizal; Olimsar, Fredy (Jurnal Akuntansi Kompetif, 2025)
This study aims to examine the effect of Accounting Conservatism, Inventory Intensity, Capital Intensity, and Fixed Asset Intensity on Tax Avoidance. The variables studied are Accounting Conservatism, Inventory Intensity, Capital Intensity, and Fixed Asset Intensity as independent variables, while tax avoidance is the dependent variable. This research uses a quantitative method. The population consists of companies listed in the Jakarta Islamic Index (JII) 70 on the Indonesia Stock Exchange during 2021-2023. The sample includes 42 companies selected using purposive sampling. The data used are secondary data obtained from the official website of the Indonesia Stock Exchange. The analysis technique applied in this study is multiple linear regression with the help of IBM SPSS 25 software. The results show that inventory intensity has a significant positive effect on tax avoidance, fixed asset intensity has a significant negative effect on tax avoidance, while accounting conservatism has no positive effect on tax avoidance, and capital intensity has no negative effect on tax avoidance. The variables of accounting conservatism, inventory intensity, capital intensity, and fixed asset intensity simultaneously have an effect on tax avoidance.